THE LEVEL OF SATISFACTION OF WITHMOORING SERVICES AT THE COASTEL FISHING PORT OF CAROCOK TARUSAN SOUTH COAST DISTRICT WEST SUMATERA PROVINCE - Rossy Sri Rahmadani; Jonny Zain; Nofrizal Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThe purpuse of this study was to determine the level of satisfaction of fisherman with mooring service at the carocok tarusan coastel fishing port (PPP).  The method used in this research is the survey method.  The survey in this study is about the level of satisfaction of fisherman with mooring services at the Carocok Tarusan beach fishing port.  The method of data collection in this research is by statified random sampling.  The data collection used in this study is primary dan secondary data.  The first stage of data prosessing is through the process of testing the validity and reliability first.  After the question naire is declared valid, then measurement are carried out using analysis custumer satisfaction index and performance analysis.  Custumer Satisfaction Index used to determine the level of attributes and services of mooring service while it is used to analyze custumer satisfaction with a product of service, from the result of this study, the level of satisfaction of fisherman with mooringservices at PPP Carocok Tarusan with the CSI analysis method is 91,08 %.  Which means the level of satisfaction is the very satisfactory category.Keyword :Survey,Customer Statisfaction Index, Importance Analysis